Molecular analysis of the rDNA ITS-1 intergenic spacer in Drosophila mulleri, D-arizonae, and their hybrids - Baffi, M. A.; Ceron, C. R. (Kluwer Academic/plenum Publ, 2002)
We analyzed the ITS-1 spacer region of the rDNA in Drosophila mulleri and D. arizonae, two sibling species belonging to the mulleri complex (repleta group) and in hybrids obtained in both cross directions. In spite of several previous studies showing the incompatibility of crosses involving D. arizonae females and D. mulleri males, we were able to obtain hybrids in this direction. Complete ITS-1 region was amplified using primers with homology at the 3'-end of the 18S rDNA and the 5'-end of the 5.8S rDNA genes. Our data demonstrated that D. mulleri and D. arizonae can be differentiated as they present a difference in length for the ITS-1 region. The amplified fragment for this region in D. mulleri has a length of 600 bp, whereas in D. arizonae this fragment is about 500 bp. It was also observed that male and female hybrids obtained in both cross directions present two amplified fragments, confirming the location of the ribosomal cistrons in the X chromosomes and microchromosomes of both parental species.
Keywords: ribosomal DNA; ITS-1 spacer; Drosophila mulleri; D. arizonae; interspecific hybrids